2012
DOI: 10.1088/0953-2048/25/8/084022
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of the superconducting properties of FeSe0.5Te0.5thin films through the substrate effect

Abstract: Using a field-effect transistor (FET) configuration with solid Li-ion conductor (SIC) as gate di-electric, we have successfully tuned carrier density in FeSe0.5Te0.5 thin flakes, and the electronic phase diagram has been mapped out. It is found that electron doping controlled by SIC-FET leads to a suppression of the superconducting phase, and eventually gives rise to an insulating state in FeSe0.5Te0.5. During the gating process, the (001) peak in XRD patterns stays at the same position and no new diffraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
69
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 60 publications
(108 reference statements)
10
69
0
Order By: Relevance
“…2. At the same time, the relation between the T c and Z Se/T e (and also Fe-Se and Fe-Te bond lengths) is clearly linear, as was reported for FeSe 0.5 Te 0.5 thin films deposited on e.g., LaAlO 3 or SrTiO 3 [18,19]. Hydrostatic pressure of 2 GPa, investigated here, is related just to the maximum of bulk T c [14], whereas other values of stress were chosen arbitrarily.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…2. At the same time, the relation between the T c and Z Se/T e (and also Fe-Se and Fe-Te bond lengths) is clearly linear, as was reported for FeSe 0.5 Te 0.5 thin films deposited on e.g., LaAlO 3 or SrTiO 3 [18,19]. Hydrostatic pressure of 2 GPa, investigated here, is related just to the maximum of bulk T c [14], whereas other values of stress were chosen arbitrarily.…”
Section: Resultssupporting
confidence: 77%
“…In turn, non-hydrostatic strains also modify T c of the 11-type superconductors as it was revealed in lattice mismatched epitaxial films where tensile strain suppresses superconductivity (SC) [16,17]. It was an opposite effect to that of the compressive biaxial (ab-plane) [17,18,19] or uniaxial (c-axis) [20] strain, causing the increase of the T c 's.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In FeSe tensile strain strongly decreases T c [4] but all kinds of compressive strain lead to an increase of its T c [4,5,6,7,8,9,10,11,12,13]. The influence of strain on SC of iron chalcogenides is somewhat related to the changes of tetrahedral coordination of Fe atoms [10,5,12]. Furthermore, a magnetic order of particular compounds is also connected with chalcogen atom position in the unit cell (u.c.)…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the films with best superconducting properties, are on LAO and MgO, whose the lattice misfit parameter M ≡ (a sub − 3.798)/a sub = -0.21% and 9.82%, respectively. It should be noted that Bellingeri et al reported positive correlation between the in-plane lattice parameters of the films and the substrates [99], while their films were not coherently strained to the underlying substrates. The discrepancy between the observed results may result from the difference of the growth temperatures; Bellingeri et al grew the films at much higher temperature of 550 • C than Imai et al (300 • C) [52].…”
Section: -Systemmentioning
confidence: 94%